The effect of incorrect scanning distance on boundary detection errors and macular thickness measurements by spectral domain optical coherence tomography: a cross sectional study - Varga, Boglárka Enikő; Tátrai, Erika; Cabrera DeBuc, Delia; Somfai, Gábor Márk (BMC ophthalmology, 2014)
Background To investigate the influence of scan distance on retinal boundary detection errors (RBDEs) and retinal thickness measurements by spectral domain optical coherence tomography (SD-OCT). Methods 10 eyes of healthy subjects, 10 eyes with diabetic macular edema (DME) and 10 eyes with neovascular age-related macular degeneration (AMD) were examined with RTVue SD-OCT. The MM5 protocol was used in two consecutive sessions to scan the macula. For the first session, the device was set 3.5 cm from the eye in order to obtain detectable signal with low fundus image quality (suboptimal setting) while in the second session a distance of 2.5 cm was set with a good quality fundus image. The signal strength (SSI) value was recorded. The score for retinal boundary detection errors (RBDE) was calculated for ten scans of each examination. RBDE scores were recorded for the whole scan and also for the peripheral 1.0 mm region. RBDE scores, regional retinal thickness values and SSI values between the two sessions were compared. The correlation between SSI and the number of RBDEs was also examined. Results The SSI was significantly lower with suboptimal settings compared to optimal settings (63.9±12.0 vs. 68.3±12.2, respectively, p = 0.001) and the number of RBDEs was significantly higher with suboptimal settings in the “all-eyes” group along with the group of healthy subjects and eyes with DME (9.1±6.5 vs. 6.8±6.3, p = 0.007; 4.4±2.6 vs. 2.5±1.6, p = 0.035 and 9.7±3.3 vs. 5.1±3.7, p = 0.008, respectively). For these groups, significant negative correlation was found between the SSI and the number of RBDEs. In the AMD group, the number of RBDEs was markedly higher compared to the other groups and there was no difference in RBDEs between optimal and suboptimal settings with the errors being independent of the SSI. There were significantly less peripheral RBDEs with optimal settings in the “all-eyes” group and the DME subgroup (2.7±2.6 vs. 4.2±2.8, p = 0.001 and 1.4±1.7 vs. 4.1±2.2, p = 0.007, respectively). Retinal thickness in the two settings was significantly different only in the outer-superior region in DME. Conclusions Optimal distance settings improve SD-OCT SSI with a decrease in RBDEs while retinal thickness measurements are independent of scanning distance.